Taxonomic status of Tropiocolotes cf. steudneri with a description of a new species of Tropiocolotes (Reptilia: Squamata: Gekkonidae) in southern Iran - Rajabizadeh, Mahdi; Faizi, Hiva; Anderson, Steven C.; Zarrintab, Mohammad; Nazarov, Roman (Zootaxa, 2018)
We review the status of an Iranian gecko population previously referred to Tropiocolotes cf. steudneri and describe it as a new species, Tropiocolotes hormozganensis sp. nov. We discuss the taxonomic history of this population and compare its characters with those of the other species in the genus. The new species is distinguished from other species of Tropiocolotes by possessing weakly keeled dorsal scales and smooth ventral scales, having imbricate scales on dorsal and ventral tail, possessing clearly tricarinatesubdigital scales, 48–55 dorsal scales, two pairs of postmental shields, of which the second pair is about half of the size of the first, 100–107 scales longitudinally along underside of body, 15–19 scales across head and 16–19 subdigital lamellae.